2019
DOI: 10.1186/s12870-019-2081-7
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy and RNA-Seq reveal important gene pathways regulating sex differentiation in a functionally Androdioecious tree, Tapiscia sinensis

Abstract: BackgroundGametogenesis is a key step in the production of ovules or pollen in higher plants. The sex-determination aspects of gametogenesis have been well characterized in the model plant Arabidopsis. However, little is known about this process in androdioecious plants. Tapiscia sinensis Oliv. is a functionally androdioecious tree, with both male and hermaphroditic individuals. Hermaphroditic flowers (HFs) are female-fertile flowers that can produce functional pollen and set fruits. However, compared with mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 118 publications
2
11
0
Order By: Relevance
“…In previous studies, our results showed that bisexual flowers are the ancestral condition in T. sinensis 4 6 . Loss of female function may be the consequence of a large-scale insertion into TsRPL10A that caused the development of a sterile pistil in the hermaphroditic flower primordium (Figs.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…In previous studies, our results showed that bisexual flowers are the ancestral condition in T. sinensis 4 6 . Loss of female function may be the consequence of a large-scale insertion into TsRPL10A that caused the development of a sterile pistil in the hermaphroditic flower primordium (Figs.…”
Section: Discussionsupporting
confidence: 55%
“…
Fig. 3 Floral morphology and development of Tapiscia sinensis 5 , 6 . A Hermaphroditic T. sinensis individual showing the simultaneous occurrence of flowers and fruit.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…STM is playing an essential role in stopping the differentiation of meristem cells through cytokinins production. It maintains the shoot apical meristem development and function (Xin et al, 2019). PRC2 gene (FIE) is involved in the development of shoot through controlling STM expression and other class 1 KNOX genes.…”
Section: Histone Methylation and Ubiquitinationmentioning
confidence: 99%
“…Androdioecy is an exceedingly rare mating system in which males and hermaphrodites co-occur in a single population with normal sexual function [1]. Androdioecious plants are extremely rare in nature, less than 50 plants have been reported worldwide such as Datisca glomerata [2], Mercurialis annua [3], Pseudoxandra spiritus-sancti [4] and Tapiscia sinensis [5,6], drawing widespread interests by scientists. Surprisingly, such an unusual breeding system prefers to be distributed in the Oleaceae species including Phillyrea latifolia [7], Phillyrea angustifolia [8], Fraxinus lanuginose [9], Chionanthus retusus [10], Osmanthus serrulatus [11], O. delavayi [12] etc., accompanied by higher frequencies of males compared to other androdioecious species [13].…”
Section: Introductionmentioning
confidence: 99%